Persepsi Peserta Didik Terhadap Kompetensi Profesional Guru Bahasa Arab - Ratna Ahmadi; Ayuba Pantu; Herson Anwar; Abdullah (Faculty of Education and Teacher Training, 2022)
This Skripsi discusses the students' perception on a professional teacher in Arabic learning at class VIII Madrasah Tsanawiyah Al-Falah Kec. Limboto Barat. The problems in this research were: (1) how is the students' perception on Arabic teacher? (2) What are the professional teachers' inhibitors and efforts in Arabic Learning? The aims of this research were: (1) To know the students' perception on Arabic teacher. (2) To know the professional teachers' inhibitors and efforts in Arabic Learning. This research was a descriptive qualitative research which clearly described all events, things, and situations to an object that researched. The data resources were taken from students, Arabic teachers, and the headmaster of Madrasah Tsanawiyah Al-Falah Limboto Barat. Based on the research result, it was found that the students had a good perception on a professional teacher in Arabic learning. It was proven by the teacher ability related to the behavior and performance so the teacher become a good example for the students, mastering the related science, planning the lesson, evaluating, and understanding the students, communicating with the students, teachers, students' parents or society. The problems found by the researcher were: (1) During the Arabic learning, most of the students could not translate the Arabic sentence well; (2) The lack of school administration and lesson books.